1994
DOI: 10.1097/00002030-199411004-00082
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions With Zidovudine Phosphorylation in Vitro

Abstract: We have investigated the effect of a range of drugs (some commonly coadministered with zidovudine [ZDV] to human immunodeficiency virus-positive patients) on intracellular phosphorylation of ZDV by stimulated peripheral blood mononuclear cells, Molt 4 cells, and U937 cells in vitro. Of the drugs tested (azoles, antiviral agents, antibiotics, and anticancer agents), only doxorubicin and ribavirin caused inhibition of anabolite formation as measured by high-performance liquid chromatography. This in vitro approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…The antiviral agent ribavirin and the anticancer drug doxorubicin have been previously shown to inhibit phosphorylation of ZDV in PBMCs, Molt 4, U937 and H9 cells in vitro (Vogt et al, 1987;Hoggard et et., 1995). Altered phosphorylation is the most probable explanation for the decreased anti-HIV activity of ZDV in the presence of ribavirin in MT-4 cells (Baba et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiviral agent ribavirin and the anticancer drug doxorubicin have been previously shown to inhibit phosphorylation of ZDV in PBMCs, Molt 4, U937 and H9 cells in vitro (Vogt et al, 1987;Hoggard et et., 1995). Altered phosphorylation is the most probable explanation for the decreased anti-HIV activity of ZDV in the presence of ribavirin in MT-4 cells (Baba et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin has now been shown to inhibit phosphorylation of both ZDV (Hoggard et al, 1995) and ddC; however the inhibitory effects are not thought to be due to the cytotoxicity of the drug since cell viability, as measured by trypan blue and neutral red uptake is unaffected at the highest concentration used. Although the exact mechanism of inhibition of dideoxynucleoside phosphorylation is not clear, it is unlikely to be a specific inhibitory effect on the kinases involved in the phosphorylation pathways since ddC and ZDV are phosphorylated by different enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of drug interactions have proven to be beneficial in predicting which drug combination regimens should be evaluated in a clinical setting (5,6,8). In the present study, we have evaluated in vitro the interactions between TAK-220 and representatives of each class of currently available antiretroviral agents.…”
Section: Tak-220 Is a Ccr5 Antagonist Part Of The New Class Of Anti-mentioning
confidence: 99%
“…This is because thymidine kinase has a 600-fold higher af®nity for ZDV than d4T. The clinical effect of this interaction was seen in ACTG 290, when the ZDV plus d4T arm was discontinued after interim analysis demonstrated that subjects receiving this combination had signi®-cantly greater decreases in CD4 counts than the other arms [195].…”
Section: Nucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 99%